Come To PaPa T-Shirt Printing Services - Alimudin, Andi Mohd Nur Baihaqi; Simpul, Amsler; Ag Yusof, Ag Yazid; Sufian, Mohd Danish; Hamzah, Mohd Asri; Matlin, Mohd Firdaus (2019)
Our business is based on partnership where we are consisting 6 members which hold important position in the company such as, general manager, administrative manager, marketing manager, operational manager and financial manager. The business capital in our company is RM20,000, which is every member have their own contribution which are RM3340 for each member equivalent to RM20,040 and the RM 40 we took it as an additional. Our business is located at Sulaman Sentral, Kota Kinabalu Sabah, we are choosing this location because it is a strategic places and one of the place that consist big amount of people that are suitable to be our customer. Our company is more focusing on providing a shirt printing service and provide plain T-shirt that is good in term of quality. Our company will provide a plain of shirt that the customers can order and ask to be printed such as name, number and logo. What make our company different from others is we are providing services of customization, meaning to say customers can pick the pattern, colour and else for their shirt. For the T-shirt we make it more durable than the other because we can see that it is our opportunity to start our business. We have found that the T-shirt nowadays is not durable and easy to tear, so we can see that it is our chance to make the T-shirt that more suitable with the customer need and demand. To make our product more attracting and more interesting, we decided to provide product customization from customer, which is the customers themselves can request their own design that they want such as in term of size, shape, and colouring. We are also providing delivery services to the customers that live nearby from our company. In order to do that, we have already prepared our company with vehicle to deliver our product to the customers. We expect that our business will become more developed in the future because with the new innovation on our printing service and also T-shirt that we provide, the demand from customer will increase time by time. This will give more advantages for us to make our product more profitable in long term.